Students as partners in quality assurance: implications for higher education - Umar, Mwebesa; Mohd. Asraf, Ratnawati (American Scientific Publishers, 2018)
The implementation of a Quality Assurance System (QAS) ought not to be the responsibility of only the administrative members of the institution. To realize effective functional mechanisms of QAS in institutions of higher learning, there should be direct involvement of students in the system. Students play a vital role in not only checking the excesses of the administrators but also feel the need to keep the quality standards of their institution. When students get involved in the QAS of their institution, they fully own the decisions, policies, and regulations that govern such an institution. This paper advocates the involvement of students in QAS and suggests the areas in which they can best contribute.